Late Pleistocene to Holocene paleoenvironmental evolution of Lake Hazar, Eastern Anatolia, Turkey - Eris, Kursad Kadir; On, Sena Akcer; Cagatay, M. Namik; Ulgen, Umut Baris; On, Zeki Bora; Gurocak, Zulfu; Okan, Ozlem Oztekin (Pergamon-Elsevier Science Ltd, 2018)
High-resolution seismic reflection profiles and core analyses in Lake Hazar provide a detailed record of the lake level fluctuations and the robust chronology of paleoclimatic events of the Eastern Anatolia during the late Pleistocene to Holocene. The earlier period of Marine Isotope Stage 3 (MIS-3) prior to 48 cal ka BP was accompanied by considerable lake level drop below 95 m, whereas the lake level increase during the later period (ca. 48-29 cal ka BP) gave rise to deposition of a transgressive unit with typical of aggradational architecture in the seismic reflection profiles. High climate variability with the Greenland interstadials and stadials (Dansgard-Oeschger and Heinrich events) in Lake Hazar are sensitively recorded in the core sediments by using multi-proxy analyses. Adjustment of seismic units correlating with the radiocarbon-dated chronostratigraphic units in the studied cores implies that the early Marine Isotope Stage 2 (MIS-2) is marked by an another lowstand lake level existed at ca. -90 m during 29-23 cal ka BP. In comparision to MIS-3 stage, the multi-proxy analyses reveal a general dry evaporative condition during most of the Last Glacial Maximum. In Lake Hazar, the maximum humidity in the late glacial period existed during 14.9-13.5 cal ka BP. The existence of a hiatus in the sedimentary record is documented in the seismic data that coincides with the cold and dry Younger Dryas period, implying a remarkable lake level drop. The multi-proxy records of the Holocene sediments reveal that a maximum precipitation in the early Holocene period prevailed during 10.1-9.3 cal ka BP, leading water level rise in the lake. In Lake Hazar, the middle Holocene until 4.9 cal ka BP is represented by highly climate variations, indicating a series of shorter wet and longer dry climate periods. The late Holocene is accompanied by lake level rises under a general wet climate condition that was interrupted by short dry climate intervals during 3.7-3.3 cal ka BP, 2.8-2.6 cal ka BP and 2.1-1.8 cal ka BP. (C) 2017 Elsevier Ltd and INQUA. All rights reserved.
Workshop on Paleoclimatic and Paleoecological Studies in Turkey's Lakes (TURQLAKES) -- JUN 21-23, 2016 -- Ardahan Univ, Ardahan, TURKEY
Keywords: High-Resolution; Climatic-Change; Record; Van; Sediments; Pollen; Basin; Cave; Sea; Stratigraphy